Mechanisms for introduction of pseudo ductility in fiber reinforced polymer composites- a review - Vinayak S. Uppin; P. S. Shivakumar Gouda; I. Sridhar Research Center, Department of Mechanical Engineering, SDM College of Engineering and Technology, Dharwad, Visvesvaraya Technological University, Karnataka, India. (Fracture and Structural Integrity)
Advanced polymer matrix composites are gaining the market in their way due to their exceptional specific stiffness, specific strength, fatigue, and corrosion resistance in the field of Auto-Tech, Aero-Tech, Biotech, etc. However, the lack of ductility and catastrophic failure has limited their application in these areas. Hence there is a need to explore the state of art technological developments in designing toughened composites by minimizing their factor of safety. A new generation of high-performance composites with pseudo-ductile or ductile behavior is essentially required for the fiber-reinforced composite structures to mitigate the catastrophic failures. The present High-Performance Ductile Composite Technology (HiPerDuCT) program is jointly between the University of Bristol U.K and Imperial College London working to address this challenge by developing newer materials. The various fiber architectures made under this project gave a more gradual failure rather than catastrophic failure with improved mechanical properties. This review mainly focuses on summarizing the pseudo ductility evolution in fiber-reinforced composites by eminent researchers with a possible alternative like fiber positions in matrix materials for introducing reasonable ductility in composites.